Evaluation of the proinflammatory effects of contaminated bathing water. Issue 20 (18th October 2019) - Sattar, Anas A.; Abate, Wondwossen; Fejer, Gyorgy; Bradley, Graham; Jackson, Simon K.
ABSTRACT: Contaminated marine bathing water has been reported to adversely affect human health. Our data demonstrated a correlation between total endotoxin (lipopolysaccharide; LPS) levels and degree of contamination of marine bathing waters. To assess the potential health implications of LPS present in marine bathing waters, the inflammation-inducing potency of water samples collected at different time points at multiple sampling sites were assessed using a cell culture-based assay. The numbers of fecal indicator bacteria (FIB) were also examined in the same samples. Water samples were used to stimulate two cell culture models: (1) a novel non-transformed continuously growing murine cell line Max Plank Institute (MPI) characteristic of alveolar macrophages and (2) human MonoMac 6 monocyte cell line. The inflammatory potential of the samples was assessed by measuring the release of inflammatory cytokines. The presence of high levels of LPS in contaminated bathing water led to induction of inflammatory response from our in vitro cell-based bioassays suggesting its potential health impact. This finding introduces an in vitro culture assay that reflects the level of LPS in water samples. These observations further promote previous finding that LPS is a reliable surrogate biomarker for fecal contamination of bathing water.